Integrasi Nilai-nilai Sosial Kearifan Lokal Gawe Musim Kembalit dalam Pembelajaran IPAS SDN 2 Sakra - M. Abd. Mutholip; Habibuddin Habibuddin; Yul Alfian Hadi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This research aims to describe the integration of local wisdom values of the Gawe Musim Kembalit as a learning resource for natural and social science at SD Negeri 2 Sakra, Sakra District, East Lombok Regency. This type of research uses descriptive qualitative research methods with the research subjects being class IV teachers and class IV students, while the data collection techniques used are observation, interviews and direct documentation to obtain the required data. Data were analyzed using data analysis techniques according to Milles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the values of local wisdom of the Gawe Musim Kembalit are very important to be integrated in learning, especially in science and science learning because they have to know their own culture and environment. Integrating local wisdom with students is one way to preserve the culture of the Sasak tribe so that they can avoid the erosion of culture due to globalization. Through integration it can have a good impact on the formation of student characteristics.